INTERCALATION OF OLYGOMER OF HYDROXYL-CHROMIUM INTO NATURAL KAOLINITE - Rodiansono Rodiansono; Reda Ariyantie; Abdullah Abdullah (Universitas Gadjah Mada, 2008)
Preparation of a kaolin-hydroxyl chromium composite and characterization of its physico-chemical properties were conducted. The olygomer hydroxyl-chromium was prepared by adding Na2CO3 to 0.1 M chromium nitrate solution (ratio OH/Cr = 2) and then dried at 110 oC and 400 oC for 4 h. Characterization of kaolin-hydroxyl chromium composite includes determination of acidity, functional groups, basal spacing, and surface area (BET-N2 sorption analyzer). The result showed that intercalation of hydroxyl chromium resulted in the decreasing of basal spacing but increased the specific surface area of kaolin. Drying of the intercalated kaolin at 400 oC decreased surface area, total volume pore and pore radius. FT-IR spectra showed that hydroxyl-chromium detected at wavelength of 2925 and 2855 cm-1.